PERSAINGAN ANTAR WARUNG KOPI BERAKIBAT WARUNG KOPI GAUL SECARA BERTAHAP MENGALAMI PENURUNAN PROFITABILITAS USAHA - Daren Zhu Putra; Dian Sudiantini, Desta Dima Maulana, Randy Saputra, Sutrio Hotasi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research aims to analyze the impact of competition between coffee shops on the decline in profitability of the local coffee shop business. In recent years, the existence of social coffee shops has become increasingly widespread and has become an integral part of people's lifestyle. However, intense competition, both from franchise branded coffee shops and specialty local coffee shops, has significantly affected the profitability of local coffee shop businesses. The research method used in this study is qualitative research with a Gap Research approach. The research results show that increasingly fierce competition has resulted in a significant decrease in the number of customers at local coffee shops. Factors such as product innovation, pricing strategy, business location, and promotion play an important role in determining the competitiveness of a coffee shop. Apart from that, changes in consumer preferences towards more modern and well-equipped coffee shops have also contributed to the decline in profitability of popular coffee shops. This research concludes that local coffee shops need to adapt to market dynamics and continue to improve service quality and product innovation to survive amidst intense competition.